2020
DOI: 10.1038/s41598-020-70799-0
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis and mortality prediction of sepsis via lysophosphatidylcholine 16:0 measured by MALDI-TOF MS

Abstract: Sepsis remains a critical problem with high mortality worldwide, but there is still a lack of reliable biomarkers. We aimed to evaluate the serum lysophosphatidylcholine (LPC) 16:0 as a biomarker of sepsis using matrix-assisted laser desorption/ionization time-of-flight mass spectrometry (MALDI-TOF MS). Patients admitted to intensive care unit at Severance Hospital from March 2017 through June 2018 were prospectively enrolled. The inclusion criteria were the fulfillment of at least two criteria of systemic inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…Another source of monolaurin could be from the degradation of lysophosphatidylcholine 12:0 (LPC12:0). Increased levels of LPCs were found in COVID-19 patients, while another study reported that decreased concentration of LPC16:0 could be a useful biomarker for sepsis diagnosis and mortality prediction in intensive care unit patients 34 .…”
Section: Discussionmentioning
confidence: 96%
“…Another source of monolaurin could be from the degradation of lysophosphatidylcholine 12:0 (LPC12:0). Increased levels of LPCs were found in COVID-19 patients, while another study reported that decreased concentration of LPC16:0 could be a useful biomarker for sepsis diagnosis and mortality prediction in intensive care unit patients 34 .…”
Section: Discussionmentioning
confidence: 96%
“…Consistently, we found that plasma LPC(14:0) concentrations were decreased in patients with BaPn. LPCs have also been proposed as useful biomarkers for diagnosing sepsis and predicting patient mortality 28 , while metabolomics and lipidomics screening have recently revealed decreased serum LPC levels in patients with COVID-19 with lung injury 29,30 . Our results further strengthen the association between blood LPC levels and acute inflammation.…”
Section: Discussionmentioning
confidence: 99%
“…Respiratory and renal failure, together with the occurrence of sepsis, could be confounding factors. It may be that some alteration of specific LPCs (e.g., LPC 16:0) is driven by sepsis, ( 46 ) in addition to hepatic and nonhepatic modulation of the LPC‐ATX‐LPA axis. Our data demonstrate that monocytes themselves up‐regulate ATX/ENPP2 expression following LPS stimulation, which could alter the lipid profile of their immediate microenvironment.…”
Section: Discussionmentioning
confidence: 99%